Comprehension of linear systems with two unknowns in secondary education - Juan Carlos Martín Molina; Alexander Maz-Machado; María José Madrid; María Josefa Rodriguez-Baiget (Institute of Advanced Engineering and Science, 2024)
Over the past few years, teachers and researchers in mathematics education have emphasized the importance of students acquiring a comprehensive understanding of mathematics. However, during the process of learning mathematics in secondary education, some students encounter difficulties with various algebraic concepts. This article presents the key aspects of a descriptive and exploratory study conducted with two groups of Spanish students in the 4th year of secondary education, using a local model to interpret and evaluate their comprehension of linear systems of two equations with two unknowns. This research offers insights into the phenomenological, epistemological, and cognitive aspects exhibited by the students. In particular, the analysis focuses on the conceptual content of the students’ productions. Consistent with similar studies, the results indicate that the students’ comprehension of this algebraic knowledge is mainly technical, rote-based and non-meaningful, although some differences exist between the two groups under consideration. Furthermore, the article discusses how these findings may impact the design and implementation of educational proposals focused on improving students’ comprehension of this knowledge.